Understanding Happiness: A Study on the Influence of Emotional Intelligence and Life Satisfaction in Adults - Tapia Salas, Elizabeth Gloria (2024)
The main purpose of this study focuses on developing an explanatory model of subjective happiness in adults in Tacna, integrating emotional intelligence and life satisfaction as central variables. The sample included 191 adults from Tacna, with a gender distribution comprising 54% women and 46% men. Three structural equation models were applied to examine subjective happiness in this population. In Model 1, a Chi-square ratio over degrees of freedom (X2/GL) of 1.644 was recorded, with a Comparative Fit Index (CFI) of 0.933, a Tucker-Lewis Index (TLI) of 0. 919 and a Parsimony-Normed Fit Index (PNFI) of 0.702. In Model 2, after the elimination of one predictor, an X2/GL of 1.527, CFI of 0.951, TLI of 0.939 and PNFI of 0.709 were observed. By incorporating a covariance in Model 3, improvements were evident, with an X2/GL of 1.438, CFI of 0.959, TLI of 0.949 and PNFI of 0.706. The most significant correlation was observed between subjective happiness and emotional intelligence, with a p-value of 0.004. No significant differences in happiness, intelligence and satisfaction were found between women and men when comparing by gender. These results indicate that Model 3 presents the strongest fit and a significant correlation between happiness and emotional intelligence.